Correlation analysis between single nucleotide polymorphism of interleukin-1ß gene and interleukin-1 concentration in three chicken breeds - XIANGPING, LIU; CUNBO, WANG; GUOBIN, CHANG; KEHUA, WANG; GUOHONG, CHEN; TAOCUN, DOU; LIANG, QU; TENG, MA; RONG, CHEN (The Indian Journal of Animal Sciences, 2013)
This paper aims to detect single nucleotide polymorphism (SNP) of interleukin-1ß (IL-1ß) gene of chicken and findgenetic marker of IL-1 concentration traits. SNPs of IL-1ß gene and IL-1 concentration in blood serum in Rugao (RG),Wenchang (WC), and Anka Chicken (AK) were detected by SSCP-PCR and ELISA, respectively. The results showedthat IL-1 concentration in blood serum of AK was extremely significantly higher than that of RG and WC. Four mutationswere found in all 3 breeds, G476A, T482C, C1215T and T1507C. The genotype distribution of RG chicken at site nt476was extremely significantly different from WC and AK, whereas there was no significant difference between WC andAK. Significant correlations were found between C1215T and IL-1 concentration in 3 chickens breeds, showing thatIL-1 concentration of TT genotype chicken was significantly higher than that of CC. The results demonstrated that thegenotype distributions at SNP sites presented significant difference among three breeds, and the site nt1215 could be a genetic marker of IL-1 concentration traits in RG.